2022
DOI: 10.3390/foods11030422
|View full text |Cite
|
Sign up to set email alerts
|

The Quality and Functional Improvement of Retorted Korean Ginseng Chicken Soup (Samgyetang) by Enzymolysis Pre-Treatment with Cordyceps militaris Mushroom Extract

Abstract: This study aimed to investigate the functional and quality improvement of retorted Korean ginseng chicken soup that was hydrolyzed using a single extract from Cordyceps militaris (CM) mushroom, or in combination with bromelain, flavorzyme, or a mix of both. A total of 36 fat-trimmed breast meat from commercial broilers were hydrolyzed with one of six treatments, (1) flavorzyme as a positive control (PC), (2) no addition as negative control (NC), (3) crude CM extract (CME), CM extract prepared with either (4) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…Glutamic acid, serine, alanine, and lysine were the most predominant FAAs identified in this study. The total FAA concentration in the NC was recorded at 167.87 mg/100 g, in accordance with previous reports in breast meat [27]. The total FAA concentration did not differ, even after the addition of G and BG extracts (p>0.05).…”
Section: Free Amino Acid Contentssupporting
confidence: 91%
See 1 more Smart Citation
“…Glutamic acid, serine, alanine, and lysine were the most predominant FAAs identified in this study. The total FAA concentration in the NC was recorded at 167.87 mg/100 g, in accordance with previous reports in breast meat [27]. The total FAA concentration did not differ, even after the addition of G and BG extracts (p>0.05).…”
Section: Free Amino Acid Contentssupporting
confidence: 91%
“…Contrarily, with regard to the modified FAA in this study, the flavour identity of the alanine is reported to impart a sweet and pleasant flavour. Moreover, in the presence of Na salt, alanine might exhibit a synergistic effect with IMP to generate an umami flavour [26,27]. This FAA has been reported to be responsible for the major sweet flavour in crab meat [30].…”
Section: Free Amino Acid Contentsmentioning
confidence: 99%
“…In addition, the pH value of CPE in this study (2.01 is assumed to initiate the hyperacidification of phenolic acid, which affects the membrane permeability of bacteria. Hyperacidification is caused by disruption of ATP synthesis and cell death ( Barido et al, 2022 ; Cueva et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Alcalase, Flavourzyme, and Protamex were three of some common commercial proteases for food protein extract hydrolysis. The protein extracts had various origins, such as tuna stomach (Guerard et al, 2001), edible bird nest (Amiza et al, 2019), eel (Halim & Sarbon, 2017); chicken (Barido et al, 2022; Dong et al, 2020); bone marrow (Shen et al, 2019; Xu et al, 2018); bone (Chiang et al, 2018; Dong et al, 2014; Fan et al, 2018; Tishinov et al, 2010; Zhang et al, 2014), other among substrates. In those researches relevant to protein hydrolysis, hydrolyzing conditions of these enzymes were fixed or investigated.…”
Section: Resultsmentioning
confidence: 99%
“…For detail, the hydrolyzing pH of Alcalase was changed from 6 to over 9 and its hydrolyzing temperature was from 50°C to 60°C (Amiza et al, 2019; Beaubier et al, 2021; Guerard et al, 2001; Halim & Sarbon, 2017; Tishinov et al, 2010). While Protamex and Flavourzyme could hydrolyze proteins at a narrow range of pH (7–8) and an appropriate hydrolyzing temperature range was similar to Alcalase (Barido et al, 2022; Chiang et al, 2018; Dong et al, 2014; Fan et al, 2018; Shen et al, 2019; Xu et al, 2018; Zhang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%